Double versus single suture stenting to manage hypertensive spikes after glaucoma drainage device implantation. Issue 6 (November 2021) - Chemello, Francesca; Rodella, Anna; Barosco, Guido; Ceruti, Piero; Tosi, Roberto; Marchini, Giorgio
Purpose: To evaluate the safety and efficacy of double compared to single intraluminal suture stenting in reducing early postoperative hypertensive spikes (HS) and hypotony after Baerveldt glaucoma implant surgery. Methods: For this retrospective study, we reviewed the medical charts of 60 patients (60 eyes) who underwent Baerveldt drainage device surgery between 2017 and 2019. Two groups were formed according to whether a single suture stent was placed within the tube (5-0 polypropylene, 30 eyes, group 1) or a double suture (5-0 and 6-0 polypropylene, 30 eyes, group 2). Intraocular pressure (IOP) was measured at baseline, at 6 h, and on postoperative days 1, 2, 5, 7, 14, 21, 30, 60, 90, 180. The occurrence of HS (IOP ⩾ 30 mmHg), anterior chamber reformation, decompressive paracentesis, anti-glaucoma medication, and adverse events were recorded. Results: There was a greater decrease in IOP from baseline at days 1, 2, and 21 ( p < 0.05) and number of HS at 6 h ( p = 0.006) and postoperative day 1 ( p < 0.001) in group 2. The mean number of decompressive paracentesis, anterior chamber reformation procedures, and topical anti-glaucoma medications was the same in both groups; the need for oral acetazolamide was significantly lower in group 2 at days 1, 21, and 30 ( p < 0.05). Conclusions: While both stenting methods provide a gradual, controlled decrease in IOP, the double stenting technique was associated with a sooner and greater postoperative reduction in IOP and a good safety profile thanks to fewer HS in the early postoperative period and less need for oral acetazolamide.